Improving Green Cost Performance in Nickel Smelter Buildings in Accordance with Breeam Guidelines Based on Zero Energy Building (ZEB) - Arya Dwi Dharmaputra; Abdul Charis; Muhammad Rifki Rahman (Green Publisher Indonesia, 2025)
The construction of green smelters based on the need for nickel-based vehicles that continue to increase every year is a significant threat to the global environment, especially the increase in greenhouse gas emissions. To overcome this, Indonesia needs to intensify its sustainability level in all construction projects, in line with the Sustainable Development Goals 2030 target to achieve 100% new buildings based on green concepts. This study uses the concept of BREEAM-based green building with Zero Energy Building (ZEB) and analyzes data with Structural Equation Modelling – Partial Least Square (SEM-PLS). The results of the study show that green ratings can increase project costs between 7.66% and 17.91% from conventional prices. The study identified ten factors that affect the cost performance of green scale projects, including energy efficiency and emission reduction, indoor air quality, and water use efficiency. The implementation of the BREEAM concept with the ZEB method provides cost efficiency based on the certification levels achieved, ranging from PASS to OUTSTANDING, which shows potential cost savings from 4.67% to 7.96%.